Luther's Outlaw God : Volume 1: Hiddenness, Evil, and Predestination - Paulson, Steven D. (Lutheran quarterly books., 2018)
In this first of three volumes addressing Luther's outlaw God, Steven D. Paulson considers the two "monsters" of theology, as Luther calls them: evil and predestination. He explores how these produce fear of God but can also become the great and only comforts of conscience when a preacher arrives. Luther's new distinction between God as he is preached and God without any preacher absolutely frightened all of the schools of theology that preceded it, and for that matter all that followed Luther, as well. That fear coalesced in various opponents like Eck and Latomus, but in a special way in Desiderius Erasmus. For Paulson, bad theology begins with bad preaching, and since the church is what preaching does, bad preaching hides the church under such a dark blanket that it can hardly be detected. He argues that the primary distinction of naked/clothed or unpreached/preached radiates out in all directions for Luther's theology, and shows what difference this makes for current preaching. Specifically, Paulson takes up the central question of all theology (and life): What is God's relation to the law, and the law's relation to God? Luther's answers are surprising and will change the way you preach.